Diversity and Distribution of Sulfur Oxidation-Related Genes in Thioalkalivibrio, a Genus of Chemolithoautotrophic and Haloalkaliphilic Sulfur-Oxidizing Bacteria - Berben, Tom; Overmars, Lex; Sorokin, Dimitry Y.; Muyzer, Gerard (Frontiers in Microbiology, 2019)
Soda lakes are saline alkaline lakes characterized by high concentrations of sodium carbonate/bicarbonate which lead to a stable elevated pH (>9), and moderate to extremely high salinity. Despite this combination of extreme conditions, biodiversity in soda lakes is high, and the presence of diverse microbial communities provides a driving force for highly active biogeochemical cycles. The sulfur cycle is one of the most important of these and bacterial sulfur oxidation is dominated by members of the obligately chemolithoautotrophic genus Thioalkalivibrio. Currently, 10 species have been described in this genus, but over one hundred isolates have been obtained from soda lake samples. The genomes of 75 strains were sequenced and annotated previously, and used in this study to provide a comprehensive picture of the diversity and distribution of genes related to dissimilatory sulfur metabolism in Thioalkalivibrio. Initially, all annotated genes in 75 Thioalkalivibrio genomes were placed in ortholog groups and filtered by bi-directional best BLAST analysis. Investigation of the ortholog groups containing genes related to sulfur oxidation showed that flavocytochrome c (fcc), the truncated sox system, and sulfite:quinone oxidoreductase (soe) are present in all strains, whereas dissimilatory sulfite reductase (dsr; which catalyzes the oxidation of elemental sulfur) was found in only six strains. The heterodisulfide reductase system (hdr), which is proposed to oxidize sulfur to sulfite in strains lacking both dsr and soxCD, was detected in 73 genomes. Hierarchical clustering of strains based on sulfur gene repertoire correlated closely with previous phylogenomic analysis. The phylogenetic analysis of several sulfur oxidation genes showed a complex evolutionary history. All in all, this study presents a comprehensive investigation of sulfur metabolism-related genes in cultivated Thioalkalivibrio strains and provides several avenues for future research.